2017
DOI: 10.1002/mp.12278
|View full text |Cite
|
Sign up to set email alerts
|

FMEA of manual and automated methods for commissioning a radiotherapy treatment planning system

Abstract: An FMEA of treatment planning commissioning tests using automation and standardization via API scripting, preloaded, and pre-modeled standard beam data, and digital phantoms suggests that errors and risks may be reduced through the use of an ACP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…that makes it a challenging task to use equipment such as 3D water tanks for various measurements. This observation agrees well with other studies reported in the literature that demonstrate that automating the ATC process and using standard beam data reduces the probability of occurrence of errors . A comparison of using manufacturer‐supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer‐supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c‐arm linac …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…that makes it a challenging task to use equipment such as 3D water tanks for various measurements. This observation agrees well with other studies reported in the literature that demonstrate that automating the ATC process and using standard beam data reduces the probability of occurrence of errors . A comparison of using manufacturer‐supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer‐supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c‐arm linac …”
Section: Discussionsupporting
confidence: 90%
“…This observation agrees well with other studies reported in the literature that demonstrate that automating the ATC process and using standard beam data reduces the probability of occurrence of errors. 17,18 A comparison of using manufacturer-supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer-supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c-arm linac. 5 In the conventional approach of measurements of output in a c-arm linac, a reference detector is typically placed between the linac head and a water tank.…”
Section: Rankmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure mode and effects analysis (FMEA) is an established technique for methodically and prospectively identifying the risks involved in a process. This method has been used by several other groups to assess the risks of various processes in radiation oncology practice …”
Section: Introductionmentioning
confidence: 99%
“…This method has been used by several other groups to assess the risks of various processes in radiation oncology practice. [4][5][6][7][8] Our group recently developed a fully automatic treatment planning tool, the Radiation Planning Assistant (RPA). 9,10 In addition to developing algorithms to automate treatment planning, we also implemented a quality assurance (QA) program specific to the RPA in order to enhance the safety of automated planning.…”
Section: Introductionmentioning
confidence: 99%